2022
DOI: 10.1038/s41598-022-10620-2
|View full text |Cite
|
Sign up to set email alerts
|

Fruit economic characteristics and yields of 40 superior Camellia oleifera Abel plants in the low-hot valley area of Guizhou Province, China

Abstract: In this study, we assessed 26 economic characteristics and yields of the mature fruit of 40 superior Camellia oleifera Abel plants grown at the C. oleifera germplasm resource nursery in the low-hot valley area of Southwest Zuizhou, China, using principal component analysis (PCA). Correlations among the characteristics and the variability of the plants in these characteristics were also analyzed. Out of the 26 characteristics, 16 primary economic characteristics were selected for comprehensive assessment, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…As an important woody oil crop, the oil content of fresh fruit is directly proportional to oil production and economic value ( Hao et al., 2017 ). Research on fruit traits is critical and closely related to oil yield, an important breeding and variety-promotion reference ( Yang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an important woody oil crop, the oil content of fresh fruit is directly proportional to oil production and economic value ( Hao et al., 2017 ). Research on fruit traits is critical and closely related to oil yield, an important breeding and variety-promotion reference ( Yang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…FSR and DSR were negatively correlated with six phenotypic traits. Liang et al [ 20 ] studied 40 C. oleifera plants from Guizhou and found that only FSR and PT were negatively correlated, while DSR was negatively correlated with FHD. The result was probably due to the fact that the 40 C. oleifera plants came from a unique climate in low, hot valleys, exhibiting specific genotypic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The index of phenotypic and economic traits was determined using the method described by Yang et al [ 20 ]. In the ripening period, three plants of each variety were randomly selected to collect a sufficient amount of fruit in a mesh bag and marked.…”
Section: Methodsmentioning
confidence: 99%
“…These predictions are greater than those of Valente et al [11], who selected ten progenies, managed them in the same area, under the same conditions used in the present study, and reported a mean yield of 763 g•plant −1 , or 847 kg.ha −1 . Plant breeding for yield and quality traits in fruits is complex due to the polygenic nature of these traits and the existence of genetic correlations among them [38][39][40][41].…”
Section: Selection Gains In Sacha-inchi Progeniesmentioning
confidence: 99%